Lateral Mesoderm-Derived Mesenchymal Stem Cells With Robust Osteochondrogenic Potential and Hematopoiesis-Supporting Ability - Wei, Yili; Wang, Bin; Jia, Lei; Huang, Weijun; Xiang, Andy Peng; Fang, Cong; Liang, Xiaoyan; Li, Weiqiang (Frontiers in Molecular Biosciences, 2022)
Mesenchymal stem cells (MSCs) are among the most promising cell sources for the treatment of various diseases. Nonetheless, the therapeutic efficacy in clinical trials has been inconsistent due to the heterogeneity of MSCs, which may be partially attributed to their undefined developmental origins. The lateral mesoderm is also a developmental source of MSCs that constitute appendicular skeletal elements in the developing vertebrate embryo. However, it is difficult to isolate homogeneous LM-derived MSCs from bone tissues or bone marrow due to the lack of understanding of their characteristics. Herein, we successfully established an efficient differentiation protocol for the derivation of MSCs with lateral mesoderm origin from human pluripotent stem cells (hPSCs) under specific conditions. LM-MSCs displayed a Homeodomain transcription factor (HOX) gene expression pattern typical of the skeletal MSCs in long bones, and resembled bone marrow-derived MSCs (BMSCs) with regard to cell surface markers, global gene profiles, and immunoregulation activity, and a Homeodomain transcription factor (HOX) gene expression pattern typical of the skeletal MSCs in long bones. Moreover, we demonstrated that LM-MSCs possessed increased osteogenic/chondrogenic differentiation capacity and hematopoietic support potential compared to BMSCs. These homogeneous LM-MSCs may serve as a powerful tool for elucidating their precise role in bone formation and hematopoiesis, and could supply a potentially ideal cell source for therapeutic applications.